Cross-disciplinary perspectives on Nuo opera: bridging the gap between art, culture, and society in Guizhou - Zhao, Fang; Binti Husain, Adzira (Edelweiss Applied Science and Technology, 2024)
One of the most popular folk operas in China is the Nuo opera. Nuo opera, which is distinguished by its distinct elements such as vicious masks, peculiar clothing and jewelry, peculiar language spoken during performances, and enigmatic scenarios, has been named one of China’s intangible cultural legacies. The opera is a religious act that is fundamental to the Chinese folk religion known as Nuoism. Nuo opera is performed to ward off evil spirits, illnesses, and other influences. It also serves as a prayer request to the gods for favors. Nuo opera features singing and dancing, as well as masks and costumes for the performers. This research explores Nuo opera, a traditional performance art form that is deeply established in the cultural and social structure of Guizhou using a cross-disciplinary technique that unites art and culture. Sociocultural influence, the study examines how, in a setting that is changing quickly, Nuo Opera acts as an interface for social unity and cultural continuity. The distinct features that this culture exhibits, together with the numerous benefits that the society’s sustained growth has brought subsequent such as cultural, social, and economic values, among other significant elements. This study emphasizes interdisciplinary analysis, and its goals are to improve our understanding of the cultural value of Nuo Opera and provide useful insights for ensuring its persistent presence and significance in Guizhou society.